Pengaruh Aspek Assurance Dalam Kualitas Pelayanan Petugas Terhadap Kepuasan Pelanggan Krl Manggarai - Annisa Nurliza; Monica Wulandari; Fitri Khairunnisa; Citra Amalia Riyadlul Jannah; Siti Sahara (Jurnal Ilmiah Wahana Pendidikan, 2023)
People around Jakarta need transportation for mobility when leaving and returning to activities. This research includes quantitative research because the ultimate goal of this study is to test and show the influence between variables using statistical data analysis techniques. Assurance is the behavior and service provided by officers such as politeness, skill, and intelligence in answering questions given by users, this can make users trust KRL transportation services. Based on the survey results, it was found that services that were considered not to provide maximum service to their users, namely the Train Travel Punctuality Guarantee so that there was connectivity of KRL schedules with other modes of transportation.